Analisis Biaya Produksi dan Break Event Point sebagai Alat Perencanaan Laba pada Usaha Kerupuk Atom Ibu Hamisah di Desa Tarempa Barat Kabupaten Kepulauan Anambas - Hadli Lidya Rikayana Rika (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2022)
This study aims to determine the Production Cost and Break Event Point as a profit planning tool at the Atomic Cracker business of Mrs. Hamisah in the village of West Tarempa. This research was conducted in West Tarempa Village, Siantan District, Anambas Islands Regency for 2 months, namely in October and November 2020. The method used in this study was descriptive quantitative method. There are two types of data used in this study, namely primary data and secondary data. The population in this study was the Atomic Cracker business of Mrs. Hamisah and the sampling technique in this study used a saturated sampling technique. The results of this study indicate that the production cost using conventional calculations at the atomic cracker business of Mrs. Hamisah in the village of West Tarempa is Rp. 11,515,100 and in November Rp. 16,659,000, while the calculation of production costs using the Full Costing method in October is Rp. 11,633,025 and in November Rp. 116,796,919. The calculation of BEP units and BEP sales at the atomic cracker business of Mrs. Hamisah in West Tarempa Village is in October the BEP unit is 13 units and the sales BEP is Rp. 131,381, while in November the unit BEP was 13 units and the sales BEP was Rp. 125,718. The profit planning calculation for Mrs. Hamisah's atomic cracker business in West Tarempa Village in October is Rp. 20,777,721 and in November Rp. 31,166,840. Keywords: Production Cost, Break Event Point, Profit Planning